STRATEGI KOMUNIKASI PEMASARAN DIGITAL BERBASIS INFLUENCER PADA INSTAGRAM CLEO OXYGEN DALAM UPAYA MENINGKATKAN BRAND AWARENESS - Dyas Rhaka Pradika; Ratna Setyarahajoe; Fitria Widiyani Roosinda (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
The development of information technology can be accessed anytime and anywhere only by connecting to the internet. With a very large number of internet users, Indonesia is a potential market share for online shop business people. Digital media channels are online communication techniques used to achieve the goals of brand awareness, familiarity, enjoyment, and to influence buying interest by encouraging digital media users to visit the website. Cleo Oxygen chooses Instagram as a marketing communication channel and influencers as a means of promoting a product. The focus of the problem in this research is how influencer-based digital marketing communication strategies on Instagram Cleo Oxygen are in an effort to increase brand awareness. The researcher uses a qualitative method with a descriptive approach, for the theory used in this study is the theory of Viral Marketing Strategy according to Chaffey in his book. The results of the study show that the influencer-based digital marketing strategy on Cleo Oxygen's Instagram has an impact on (brand awerness) public trust in Cleo Oxygen products, and is evidenced by the large number of impressions and likes in a post where the influencer is able to influence his followers to participate. consume this Cleo Oxygen product. The positive responses in the comments column of the post show that the Cleo Oxygen product has been accepted by the public on the internet.